Descriptive analysis of female representations in the Spanish peseta (2017)
A numismatic review about Spanish peseta coins minted between 1869 and 2001 (except for the commemorative pieces) which representing female figures is presented in this scientific article. This paper attempts to locate and identify, through a simple descriptive analysis, the pieces with the aforementioned characteristics; so we can concluded that the history of the Spanish peseta s' history has a strong relationship with the image of the women. © 2017 Ediciones Hecate. All rights reserved.